Evaluation of NovaSure® global endometrial ablation in symptomatic adenomyosis: A longitudinal study with a 36 month follow-up. (August 2018) - Philip, Charles-André; Le Mitouard, Marine; Maillet, Laurine; de Saint-Hilaire, Pierre; Huissoud, Cyril; Cortet, Marion; Dubernard, Gil
Abstract: Objective: To evaluate the efficacy of NovaSure ® radiofrequency global endometrial ablation (GEA) in adenomyosis. Study design: We conducted a monocentric longitudinal cohort study at Croix-Rousse University Hospital (Lyon, France). Inclusion criteria were symptomatic adenomyosis resistant to drug therapy (dysmenorrhea and abnormal uterine bleeding (AUB)), for whom Novasure ® GEA was considered. The diagnosis of adenomyosis was based on ultrasound and/or MRI criteria. A questionnaire evaluating the symptoms was proposed to each patient before GEA and postoperatively at 6 months and 3 years. Results: Forty-three patients were included between December 2012 and May 2014, with a median age of 46.7 years. Preoperatively, 43 patients (100%) had AUB and 33 (76.7%) had dysmenorrhea, . Postoperatively, there was a significant reduction in AUB in 40 patients (−93%, 95% CI [85.3, 100], p < .00001) at 6 months, and in 29 patients (−67.4%, 95% CI [53.3, 81.6], p < .00001) at 3 years. Eleven patients (+ 25.5%, 95% CI [10.9, 40.3], p = .0055) experienced significant recurrence of AUB between 6 months and 3 years. Eighteen patients (41.9%, 95% CI [26.9, 56.8], p < .00001) experienced amenorrhea 6 months after the procedure, and 16 patients (37.2%, 95% CI [22.6, 51.8], p < .00001) at 3 years. Similarly, we observed a significant decrease of dysmenorrhea with an improvement in 20 patients (-60.6%, 95% CI [−46.7, −77.5], p = .00002) at 6 months and 17 patients (−51.5%, 95% CI [34.2, 68.8], p = .0001) at 3 years. The recurrence of dysmenorrhea between 6 months and 3 years in 3 patients (+ 9.1%, 95% CI [−8.7, +26.9], p = .44) was not significant. Eight patients (19%) had a hysterectomy during the study. Patients were 92% satisfied with the procedure. No major postoperative complication was reported after using NovaSure ® . Conclusion: NovaSure ® is effective in the treatment of painful and hemorrhagic symptoms associated with adenomyosis in both the short and long term. However, efficacy in controlling bleeding seems to decrease over time. Nevertheless, it appears to be a good alternative to hysterectomy in this indication, especially in patients close to menopause.